Assessment of prostate cancer radiotherapy using three-dimensional treatment planning technique - Fatima Jassim Mohammad Hassan; Haydar Hamza Obaid Alabedi (Journal of the Pakistan Medical Association)
Objective: To assess the available commercial treatment planning system using three-dimensional conformal radiation therapy with respect to treatment for prostate cancer patients.